(untitled) (Jurnal Bahasa, 2008)
This article discusses and analyzes the word order of numerals and classifiers in Malay noun phrase structures. The analysis of these two elements are based on four facts such as the strict orders of numerals and classifiers, the compulsory and optional characteristic of classifiers, the need for the presence of a numeral for the existence of a classifier and lastly the compatibility between a noun and a classifier A discussion of the four facts are based on X bar theory. This analysis claims that the classifier phrase creates an adjunction at the D-structure. This adjunction structure accommodates all of the four facts relating to the word order of numerals and classers that comes before a noun in the syntactic structure of a Malay noun phrase.